Diversity of honey stores and their impact on pathogenic bacteria of the honeybee, Apis mellifera. Issue 20 (26th September 2014) - Erler, Silvio; Denner, Andreas; Bobiş, Otilia; Forsgren, Eva; Moritz, Robin F. A.
Abstract Honeybee colonies offer an excellent environment for microbial pathogen development. The highest virulent, colony killing, bacterial agents are Paenibacillus larvae causing American foulbrood (AFB), and European foulbrood (EFB) associated bacteria. Besides the innate immune defense, honeybees evolved behavioral defenses to combat infections. Foraging of antimicrobial plant compounds plays a key role for this "social immunity" behavior. Secondary plant metabolites in floral nectar are known for their antimicrobial effects. Yet, these compounds are highly plant specific, and the effects on bee health will depend on the floral origin of the honey produced. As worker bees not only feed themselves, but also the larvae and other colony members, honey is a prime candidate acting as self‐medication agent in honeybee colonies to prevent or decrease infections. Here, we test eight AFB and EFB bacterial strains and the growth inhibitory activity of three honey types. Using a high‐throughput cell growth assay, we show that all honeys have high growth inhibitory activity and the two monofloral honeys appeared to be strain specific. The specificity of the monofloral honeys and the strong antimicrobial potential of the polyfloral honey suggest that the diversity of honeys in the honey stores of a colony may be highly adaptive for its "social immunity" against the highly diverse suite of pathogens encountered in nature. This ecological diversity may therefore operate similar to the well‐known effects of host genetic variance in the arms race between host and parasite.